2021
DOI: 10.3390/ijms22094571
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat Diet Aggravates Cerebral Infarct, Hemorrhagic Transformation and Neuroinflammation in a Mouse Stroke Model

Abstract: Background: Stroke in context of type 2 diabetes (T2D) is associated with a poorer outcome than in non-diabetic conditions. We aimed at creating a new reproducible mouse model of stroke in impaired glucose tolerance conditions induced by high-fat diet. Methods: Adult C57BL6 mice were fed for 2 months with either normal diet (ND) or high-fat diet (HFD). We used a model of Middle Cerebral Artery Occlusion (MCAO) for 90 min. Oral Glucose Tolerance Test (OGTT) and Insulin Tolerance Test (ITT) were used to assess p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…Studies have demonstrated that increased fat mass can provoke disorders of glucose metabolism by an array of pathways ( Song et al, 2006 ; King, 2008 ; Stienstra et al, 2010 ). In another experimental study, it is also reported that a high-fat diet could induce hyperglycemia and aggravate the growth of cerebral infarct volume ( Grisotto et al, 2021 ). In our research, we found that the excessive BMI group exactly had a higher blood glucose concentration in the first 24 h, and the level of blood glucose was also independently linked to lower 30-day mortality, but irrelevant to 90-day and 1-year mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that increased fat mass can provoke disorders of glucose metabolism by an array of pathways ( Song et al, 2006 ; King, 2008 ; Stienstra et al, 2010 ). In another experimental study, it is also reported that a high-fat diet could induce hyperglycemia and aggravate the growth of cerebral infarct volume ( Grisotto et al, 2021 ). In our research, we found that the excessive BMI group exactly had a higher blood glucose concentration in the first 24 h, and the level of blood glucose was also independently linked to lower 30-day mortality, but irrelevant to 90-day and 1-year mortality.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that diabetes is related to cerebral small vessel disease, which may impair the brain’s ability to compensate for acute ischemic insults [ 28 ]. A recent study involving a stroke model in mice with impaired glucose tolerance demonstrated that chronic hyperglycemia is significantly associated with larger infarct volume [ 29 ] and this may result in a worse outcome at 3 months [ 30 ]. In another study, researchers found that chronic pre-stroke hyperglycemia affected middle cerebral artery blood flow velocity during recovery, which might impact the functional outcomes of patients [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is characterized by chronic systemic inflammation that causes an immune response and then leads to microvascular dysfunction [ 5 ]. Studies have shown that diabetes worsens neurological damage after stroke [ 29 , 30 ]. Our research also confirmed that diabetes exacerbated CIRI and worsened ischaemic stroke outcomes.…”
Section: Discussionmentioning
confidence: 99%